Pengaruh Strategi Marketing Digital Seo, Word Of Mouth Dan Kualitas Pelayanan Terhadap Keputusan Memilih Berobat Pada Pasien Ibu Hamil Di Rsu Royal Prima Medan - Br Kaban, Fitriyana (Jurnal Maternitas Kebidanan, 2024)
This study aims to determine the effect of SEO Digital Marketing Strategy, Word of Mouth and Quality of Service on the Decision to Choose Treatment for Pregnant Women Patients at RSU Royal Prima Medan. The research was conducted on pregnant women who had been treated at RSU Royal Prima Medan. The population in the study were all pregnant women who had been treated at RSU Royal Prima in the last 2 years. The data collection method in this study is a questionnaire or questionnaire. The sampling technique used is the Random Sampling technique. Determining the number of samples in this study used the Slovin formula with an error rate of 10% so that a total sample of 67 was obtained from a total population of 196 pregnant women. Data analysis techniques used Univariate, Bivariate and Multivariate analysis with calculations using SPSS version 23. The results of the Bivariate test showed that the SEO Digital Marketing Strategy, Word of Mouth and Service Quality variables had an influence on the decision to choose with a p value of 0.004 each; 0.017 and 0.000 with a PR value of 3.407 each; 2,550 and 7,885. The results of the Multivariate analysis show that the Service Quality variable has the greatest influence on the decision to choose, with a p value of 0.000 and an Exp(B) value of 16.623 (95% CI 3.551-77.817). Kata kunci: SEO Digital Marketing Strategy, Word of Mouth, Quality of Service and Choosing Decisions: